The prize [compact disc, unabridged] : who's in charge of America's schools? - Russakoff, Dale (Dreamscape Media, 2015)
When Mark Zuckerberg announced in front of a cheering Oprah audience his $100 million pledge to transform the Newark Schools--and to solve the education crisis in every city in America--it looked like a huge win for then-mayor Cory Booker and Governor Chris Christie. But their plans soon ran into a constituency not so easily moved--Newark's key education players, fiercely protective of their billion-dollar-per-annum system. It's a prize that, for generations, has enriched seemingly everyone, except Newark's students.